2017
DOI: 10.3390/e19120666
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Component Selection Strategies in Hyperspectral Imagery

Abstract: Hyperspectral imagery (HSI) integrates many continuous and narrow bands that cover different regions of the electromagnetic spectrum. However, the main challenge is the high dimensionality of HSI data due to the 'Hughes' phenomenon. Thus, dimensionality reduction is necessary before applying classification algorithms to obtain accurate thematic maps. We focus the study on the following feature-extraction algorithms: Principal Component Analysis (PCA), Minimum Noise Fraction (MNF), and Independent Component Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
(60 reference statements)
2
11
0
1
Order By: Relevance
“…Several transforms have been proposed in the last decades to extract reliable information, reducing redundancy and noise. Traditional feature-extraction techniques, mainly applied to reduce the dimensionality of hyperspectral data, are PCA, ICA, and MNF [51].…”
Section: • Image Transformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transforms have been proposed in the last decades to extract reliable information, reducing redundancy and noise. Traditional feature-extraction techniques, mainly applied to reduce the dimensionality of hyperspectral data, are PCA, ICA, and MNF [51].…”
Section: • Image Transformsmentioning
confidence: 99%
“…We used pixel and object-based supervised classifiers [51,58,59]. Specifically, Maximum Likelihood (ML), Spectral Angle Mapper (SAM), and Support Vector Machine (SVM) algorithms were assessed.…”
Section: Classificationmentioning
confidence: 99%
“…Regarding the dimensionality reduction of CASI imagery, a selection of the suitable components was carried out analyzing the eigenvalues and the standard deviation values of the entropy (Ibarrola‐Ulzurrun et al. ). Besides, a visual assessment of the MNF components was made to determine which components are spatially coherent and which contain noise.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, Ibarrola‐Ulzurrun et al. compare the performance of different dimensionality reduction techniques and assessed strategies for selecting the most suitable number of components to increase the performance in the classification of CASI imagery. The study concluded that minimum noise fraction (MNF) was the most suitable dimensionality reduction technique, which has also been supported by other authors (Melgani and Bruzzone , Tarabalka et al.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many band selection methods have been proposed, and they can be grouped into two main categories: supervised band selection [9][10][11] and unsupervised band selection methods [12][13][14][15]. The supervised methods first divide data set into training samples and test samples.…”
Section: Introductionmentioning
confidence: 99%